Mathematical models of nonlinear uniform consensus - Saburov, Mansoor; Saburov, Khikmat (Science Society of Thailand under Royal Patronage, 2014)
We consider a nonlinear protocol for a structured time-invariant and synchronous multi-agent system. In the multi-agent system, we present opinion sharing dynamics as a trajectory of a cubic triple stochastic matrix. We provide a criterion for a uniform consensus of the multi-agent system. We show that the multi-agent system eventually reaches a consensus if either one of the following two conditions is satisfied: (i) every member of the group people has a positive subjective opinion on the given task after some revision steps or (ii) all entries of the given cubic triple stochastic matrix are positive.